Pencarian Informasi Wisata Daerah Bali Menggunakan Teknologi Chatbot - Paliwahet, I Nyoman Satria; Sukarsa, I Made; Gede Darma Putra, I Ketut (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 8, No. 3 Desember 2017, 2017)
Bali is famous for its culture, tradition, natural beauty in it. Domestic and foreign tourists are interested to visit the island of Bali as a tourist destination. Information about tourism on the island of Bali is often found from various media such as websites, newspapers, advertisements and so on that takes time in the search. Chatbot is a system based on chat that is able to answer questions in accordance with the ability implanted in it. The implementation of chatbot provides more efficient information in getting information. Chatbot designed using a matching question scheme with an existing pattern on chatbot knowledge. Pattern matching in this chatbot using one feature of MySQL that is Fulltext Search Boolean Mode. The results achieved is the application of chatbot tourist information using Fulltext Search Boolean Mode successfully applied well.